Childhood vaccination trends during 2019 to 2022 in Tanzania and the impact of the COVID-19 pandemic - Raphael Zozimus Sangeda; Daniel James; Harrison Mariki; Mbonea Erick Mbwambo; Mwendwa E. Mwenesi; Honesti Nyaki; Florian Tinuga; Daudi Peter Manyanga (Human Vaccines & Immunotherapeutics)
The COVID-19 pandemic has significantly disrupted healthcare systems at all levels globally, notably affecting routine healthcare services, such as childhood vaccination. This study examined the impact of these disruptions on routine childhood vaccination programmes in Tanzania. We conducted a longitudinal study over four years in five Tanzanian regions: Mwanza, Dar es Salaam, Mtwara, Arusha, and Dodoma. This study analyzed the trends in the use of six essential vaccines: Bacille Calmette-Guérin (BCG), bivalent Oral Polio Vaccine (bOPV), Diphtheria Tetanus Pertussis, Hepatitis-B and Hib (DTP-HepB-Hib), measles-rubella (MR), Pneumococcal Conjugate Vaccine (PCV), and Rota vaccines. We evaluated annual and monthly vaccination trends using time-series and regression analyses. Predictive modeling was performed using an autoregressive integrated moving average (ARIMA) model. A total of 32,602,734 vaccination events were recorded across the regions from 2019 to 2022. Despite declining vaccination rates in 2020, there was a notable rebound in 2021, indicating the resilience of Tanzania’s immunization program. The analysis also highlighted regional differences in vaccination rates when standardized per 1000 people. Seasonal fluctuations were observed in monthly vaccination rates, with BCG showing the most stable trend. Predictive modeling of BCG indicated stable and increasing vaccination coverage by 2023. These findings underscore the robustness of Tanzania’s childhood immunization infrastructure in overcoming the challenges posed by the COVID-19 pandemic, as indicated by the strong recovery of vaccination rates post-2020. We provide valuable insights into the dynamics of vaccination during a global health crisis and highlight the importance of sustained immunization efforts to maintain public health.